Exploring Managerial Activation Based on al-Qur’an Insights from Hamka’s Tafsir al-Azhar - Tegar Efrizal; Hamidullah Mahmud (at-Tahsin, 2026)
This study explores managerial activation within organizational contexts through the Qur’an, elucidating insights derived from Hamka’s Tafsir Al‑Azhar to conceptualize an Islamic framework for value-driven leadership. Although contemporary management research emphasizes efficiency and performance metrics, few studies integrate Qur’anic principles emphasizing collective moral action as a catalyst for organizational motivation and mobilization. Employing a qualitative, literature-based methodology, this research analyzes primary sources and supplementary secondary literature on Islamic management theory. Data collection involved systematic textual examination of selected Qur’anic verses interpreted, while comparative analysis contextualized spiritual insights within modern organizational paradigms. Data were analyzed through thematic coding and interpretive synthesis to identify key managerial constructs. Findings indicate that Qur’anic managerial principles encompass visionary leadership articulating organizational purpose, moral accountability fostering ethical decision-making, and collaborative engagement enhancing social cohesion. Ethical oversight ensures alignment with both spiritual and operational standards, while orientation toward collective welfare links organizational success to societal benefit. The study further reveals that embedding Qur’anic principles strengthens structural efficiency while cultivating ethically grounded and socially responsive leadership practices. Consequently, this research offers a conceptual contribution toward a holistic Islamic management model and recommends empirical validation of these principles across diverse organizational settings to assess applicability and impact.